PERINDUKAN JENTIK POTENSIAL DAN KEJADIAN DBD KELURAHAN BANJAREJO KOTA MADIUN POTENTIAL LARVAE BREEDING AND DENGUE HAEMORRHAGIC FEVER IN BANJAREJO, MADIUN - Kusariana, Nissa (Journal Nursing Care and Biomolecular, 2017)
Dengue Hemorrhagic Fever (DHF) was still a health problem. This disease could caused an outbreak. Increased cases of DHF was inversely proportional to the results of monitoring larvae. Number of larva free coverage wasÂ  >95 % so the number of density was low, but DHF cases still increased. The aim of this study to determined the association of potential larvae breeding and DHF. Methods: This analytic study used cross sectional design. The sample were 320 household in Banjarejo, Madiun. This study was conducted by observing water reservoirs in each household to determined the presence of larvae.Â  Results: The density of larvae was calculated by House Index (HI)=7.19%, Container Index (CI)=3.47 %, Breteau Index (BI)=7.62, Density Figure (DF)=2. This result shows the risk of DHF transmission in Banjarejo was moderate. The Container Index (CI) from obtained bathtub=5.94%. Analysis: It showed that the bath was Aedes aegyptiâs breeding potential than other containers. Chi Square test showed no association between larvae potential breeding place and DHF (p= 1.000). Discussion: There was no association between potential larvae breeding with the incidence of DHF.Â Â Â Â